Factors associated with a prolonged time to return to play after a concussion - Wang, E. X.; Hwang, C. E.; Nguyen, J. N.; Segovia, N. A.; Abrams, G. D.; Kussman, A. (The American Journal of Sports Medicine, 2022)
Background: Prognosticating recovery times for individual athletes with a concussion remains a challenge for health care providers. Several preinjury and postinjury factors have been proposed to be predictive of prolonged return-to-play (RTP) times, but the data in this area are still sparse.